The paradigm of the environmental education and social conflict in mining - Guadalupe Gómez, Enrique (2012)
Peru is a mega-diverse country in terms of its ecology, it also has a great mineralogical diversity that allows a significant increase to the mining sector and this in turn can lead to conflicts in communities and cities, whose residents are apparently threatened, because according to his conception, the mining will destroy all the flora and fauna, and it will pollute rivers and water sources. All this thought in most cases does not allow the development of mining and therefore of the country. We depart from the paradigm that only environmental education will change the mindset of the peruvian inhabitant lives in the area of influence of mine and this must be executed by universities and professionals who know the environment in the mining sector, this teaching would be responsible and well conceived, will be able to transform the perception and attitudes of the residents, opposed to mining development. It also presents aspects of environmental education in primary education and high school, the teacher training, and finally concludes that a population with strong environmental knowledge, both theoretical as practical will be in conditions of decide for itself with knowledges of cause and, opt for a mining that respects to the society and the environment, giving credit to a compatible mining with others sectors, as agricultural, cattle breeding, industrial or others, and propose the sustainable development and progress together in our country.